2006
DOI: 10.1185/030079906x99990
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of silver textile in the treatment of atopic dermatitis (AD)

Abstract: The elastic silver textile worn directly against the skin led to an impressive improvement of AD and a reduction in the use of prednicarbate ointment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 10 publications
0
56
0
3
Order By: Relevance
“…Table 76 provides the risk-of-bias assessment for the new study. This three-phase trial 344 with only 10 participants per group was difficult to interpret. The severity of eczema measured using the SCORAD index over the first 2 weeks of the trial showed a significant benefit for silver textile (p = 0.003) and regular prednicarbate ointment (p = 0.014) use over the use of non-silver textiles.…”
Section: X-static ®mentioning
confidence: 99%
See 1 more Smart Citation
“…Table 76 provides the risk-of-bias assessment for the new study. This three-phase trial 344 with only 10 participants per group was difficult to interpret. The severity of eczema measured using the SCORAD index over the first 2 weeks of the trial showed a significant benefit for silver textile (p = 0.003) and regular prednicarbate ointment (p = 0.014) use over the use of non-silver textiles.…”
Section: X-static ®mentioning
confidence: 99%
“…Juenger and colleagues 344 compared undergarments containing silver-coated nylon fibres (X-STATIC ® ; Noble Biomaterials) against either undergarments without the silver-coated fibres or a medium-potency topical corticosteroid (prednicarbate ointment) in a three-phase trial. Thirty participants were randomised to three groups; each group (n = 10) used a different comparator (silver textile, silver-free textile or prednicarbate ointment) in the first 14 days; all participants then used the silver undergarments in the second 14 days and all groups could use only prednicarbate as needed in the third 14-day phase.…”
Section: X-static ®mentioning
confidence: 99%
“…Prophylactic treatment only increases resistant rates and has no benefit on the course of disease. The use of silver-coated textiles and silk fabric with a durable anti- microbial finish is still under investigation, but seems to be promising, especially for children 72 .…”
Section: ) Control Of Bacterial Colonizationmentioning
confidence: 99%
“…10,11 To identify RCTs published prior to the CLOTHES trial, we searched the Global Resource of Eczema Trials database. 12 At the time of starting the CLOTHES trial, 14 small RCTs assessing the effects of therapeutic clothing had been published: three RCTs investigated silk clothing [DermaSilk TM (AlPreTec Srl, San Donà di Piave, Italy)]; [13][14][15] two investigated silver-coated textiles; 16,17 three investigated cellulose seaweed fibres with silver; [18][19][20] one investigated cellulose; 21 one investigated an anion textile; 22 two investigated types of ethylene vinyl alcohol fibre; 23,24 one investigated borage oil-coated garments; 25 and one investigated cotton and synthetic fibres. 26 Since the start of the trial, an additional study on chitosan-coated textiles has been published.…”
Section: Chapter 1 Introductionmentioning
confidence: 99%